The Decreasing Availability of Settlement Surfaces Affects the Transition From Larvae to Early Recruitment of the Scallop Argopecten purpuratus Through El Niño and La Niña Episodes - Avendaño, Miguel; Cantillánez, Marcela; Riascos, José M. (Frontiers in Marine Science, 2019)
Despite their importance as a larval source for the aquaculture industry in several countries, natural stocks of pectinids have been heavily impacted by a variety of natural and anthropogenic stressors. Here we studied the key transition from larvae to early recruitment using the largest natural population of the scallop Argopecten purpuratus (Lamarck, 1819) in Chile. We assessed whether thermal anomalies associated to El Niño-La Niña (EN-LN) cycle had a signal in the temperature regime at La Rinconada Marine Reserve and the consequences of this variability for the settlement of competent larvae of A. purpuratus to artificial and natural substrates in this area. For this, we gathered historical data (February 1950–December 2017) regarding satellite-derived thermal anomalies in the El Niño 1 + 2 region and in situ measurements of sea surface and bottom temperature in the study area. Moreover, we sampled the larval abundance of A. purpuratus in the water column and the settled spat on artificial collectors and on red algae Rhodymenia spp. – their natural settlement surface – between April 1996 and January 2000. Thermal anomalies associated to EN-LN cycle were strongly related to interannual changes in winter and summer temperature in Antofagasta Bay, with a clearer signal in winter than summer temperature. The increased reproductive activity during September–April seemingly foster the observed pulses in the larval abundance of A. purpuratus, as expected in a semi-enclosed system. In contrast to previous studies, the larval abundance did not show clear responses to the local EN-LN-related shifts in temperature regimes. Larval settlement of A. purpuratus in artificial collectors increased through the study period while that on Rhodymenia spp. showed a contrasting, decreasing trend. At the same time, the abundance of Rhodymenia spp. dropped continuously. All these temporal trends and our statistical analysis implied that, whether EN-LN-driven thermal shifts had an effect on the larval settlement of A. purpuratus, it is masked by the strong and continuous reduction in the availability of Rhodymenia spp. as a settlement surface. This reduction may have consequences for the stability of natural stocks of A. purpuratus in Chile.